UJI PERFORMANSI OPENPGP PADA KOMUNIKASI DATA WEB SERVICE BERBASIS RESTFULL - Muhammad Zaien; Muhammad Reza Faisal; Radityo Adi Nugroho (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2016)
The exchange of data in distributed systems that communicate using Web Service must happen , so that sensitive data will also be redeemed. Sensitive data is supposed to be secret , but when the data is transferred using a Web Service can be known, so OpenPGP encryption used to maintain the confidentiality of the data. Securing the transfer of data to using the OpenPGP encryption standard may have an impact on the performance of Web Service response time and durability in the server serving the request , so need to known the impact with testing and analysis of variance on test results . Implementation of OpenPGP to secure the transfer of data on Web Service resulting in increased response time of Web Service but the response time can still be tolerated , and this application does not significantly affect the resilience of the server serving the request . Keywords: Web Service , RESTful, OpenPGP, Security Pertukaran data pada sistem tersebar yang berkomunikasi menggunakan Web Service pasti terjadi, sehingga data yang bersifat sensitif pun juga akan ditukarkan. Data yang bersifat sensitif ini seharusnya dirahasiakan tetapi ketika ditransfer menggunakan Web Service data tersebut dapat diketahui. Sehingga diterapkan OpenPGP untuk menjaga kerahasiaan data. Pengamanan transfer data menerapkan standar enkripsi OpenPGP dapat berdampak pada performa waktu response Web Service dan ketahanan server dalam melayani request, sehingga perlu diketahui dampak tersebut dengan melakukan pengujian dan analisis varian dari hasil pengujian. Penerapan OpenPGP untuk mengamankan transfer data pada Web Service mengakibatkan bertambahnya waktu response Web Service tetapi waktu response tersebut masih dapat ditoleransi, dan penerapan ini tidak mempengaruhi secara signifikan terhadap ketahanan server dalam melayani request. Kata kunci: Web Service , RESTful, OpenPGP, Keamanan